Pengaruh Pendidikan, Kesehatan, Tenaga Kerja, dan Investasi terhadap Pertumbuhan Ekonomi di Provinsi DI Yogyakarta: Analisis Data Panel Kabupaten/Kota Tahun 2019-2023 - Anita Rizky Lestari; Naelul Padilah; Syafna Naila Zamzami; Annisa Azizah Cahyani; Syauqi Hafidz; Fitri Amalia (CV. ITTC INDONESIA, 2026)
Sustainable regional economic growth in the Special Region of Yogyakarta (DIY) is a crucial indicator heavily influenced by the quality of human resources and the adequacy of physical capital. This study aims to deeply analyze the effects of Mean Years of Schooling (MYS), Life Expectancy (LE), Labor Force Participation Rate (LFPR), and Investment on the Gross Regional Domestic Product (GRDP) in DIY Province. The unique characteristics of DIY Province as a national educational hub and a leading tourist destination underlie the main urgency of this research. This study employs a quantitative approach using panel data regression analysis with the Random Effects Model (REM) estimation, where the secondary data analyzed covers five regencies/cities in DIY Province during the 2019–2023 observation period. The simultaneous test results indicate that all independent variables collectively have a significant effect on GRDP, with a coefficient of determination (R²) of 85.99%. Partially, MYS, LE, and LFPR have positive and significant effects, with the LE component emerging as the most dominant contributing variable. Conversely, the Investment variable is found to have no significant effect, which is strongly presumed due to a time lag factor in realizing its benefits for the regional economy. These findings prove that improving human capital quality plays a much greater role in driving economic growth in DIY. Based on these results, the Regional Government of DIY is recommended to strengthen educational quality, expand formal sector employment opportunities, and design more effective investment policies to ensure optimal and sustainable benefits.